Candidemia in Pediatric Patients: Changing Pattern of Isolated Candida Species and Risk Factors in Eastern India. - Nabamita Chaudhury; Tanusri Biswas; Raston Mondal; Saswati Chattopadhyay; Deblakshmi Mandal; Nivedita Mukherjee; Arghya Nath; Soumyendranath Das (International Journal of Endorsing Health Science Research, 2023)
Background: Candidemia is a life-threatening bloodstream infection caused by Candida species and is a major concern in pediatric patients, particularly in developing countries like India. Therefore, the goals of the current study are to isolate and identify several Candida species from blood samples, link various risk factors with candidemia, and ascertain the antifungal sensitivity pattern of each species.